Islamic Management - Mohiuddin, Md. Golam (Dhaka : University Grants Commission)
Business
Keywords: Islamic Management; Planning; Organizing; Human motivation; Leadership; Islam and Scientific management; Prophet Muhammad's SAW leadership; Mosque management